1. (4x-3)(x-1)
2. Use the quadratic formula which you can find on youtube.
Factorise
4x^2-7x+3=
and
6x^2+10x-5=
Thanks
Method would be good-as I am stuck.
5 answers
Thanks,can you tell me the answer to the second one.
Ans also I got this far for the first part's method
4x^2-7x+3=
4x^2-3x-4x+3=
x(4x-3)-1(4x+3)
but there is nothing similar-how did you get (4x-3) for both of them.
4x^2-7x+3=
4x^2-3x-4x+3=
x(4x-3)-1(4x+3)
but there is nothing similar-how did you get (4x-3) for both of them.
Can someone please help-I need to do this today.
All I need is the method and answer.
All I need is the method and answer.
4x^2 - 7x + 3.
Use the AC Method:
A * C = 4 * 3 = 12 = -3 * -4,
4X^2 + (-3X + -4X) +3,
Group the 4 terms into 2 factorable pairs:
4x^2 -4x) + (-3x + 3),
Factor 4x from the 1st pair & -3 from
the 2nd pair:
4x(x - 1) + -3(x - 1),
Factor (x - 1) from each term:
(x - 1) (4x - 3).
Use the AC Method:
A * C = 4 * 3 = 12 = -3 * -4,
4X^2 + (-3X + -4X) +3,
Group the 4 terms into 2 factorable pairs:
4x^2 -4x) + (-3x + 3),
Factor 4x from the 1st pair & -3 from
the 2nd pair:
4x(x - 1) + -3(x - 1),
Factor (x - 1) from each term:
(x - 1) (4x - 3).